Nanobiomaterials Revolutionizing Biomedical Science: Special Issue—“Nanotechnology for Biomedical Applications” - Carla Sardo (Applied Sciences, 2023)
The field of nanotechnology applied to biomedicine has witnessed unprecedented growth in recent years owing to the development of new nanobiomaterials and the exploration of novel strategies for tackling medical problems at the nanoscale [...]